Two dimensional code for modeling of high ione cyclotron harmonic fast wave heating and current drive - Grekov, D.; Kasilov, S.; Kernbichler, W. (Вопросы атомной науки и техники, 2017)
A two dimensional numerical code for computation of the electromagnetic field of a fast magnetosonic wave in a tokamak at high harmonics of the ion cyclotron frequency has been developed. The code computes the finite differ-ence solution of Maxwell’s equations for separate toroidal harmonics making use of the toroidal symmetry of tokamak plasmas. The proper boundary conditions are prescribed at the realistic tokamak vessel. The currents in the RF antenna are specified externally and then used in Ampere’s law. The main poloidal tokamak magnetic field and the "kinetic" part of the dielectric permeability tensor are treated iteratively. The code has been verified against known analytical solutions and first calculations of current drive in the spherical torus are presented. Разработан двумерный код для расчёта электромагнитного поля быстрой магнитозвуковой волны в токамаках в диапазоне высоких гармоник ионной циклотронной частоты. Используя тороидальную симметрию плазмы токамака, методом конечных разностей код находит решение уравнений Максвелла для отдельной тороидальной гармоники. Граничные условия задаются на реальной стенке камеры токамака. ВЧ-антенна моделируется введением «внешнего» тока в закон Ампера. Полоидальное удерживающее магнитное поле и вклад «тепловой» части тензора диэлектрической проницаемости плазмы включены в расчёты с помощью итераций. Код был верифицирован путём сравнения расчётов с известным аналитическим решением. Представлены первые расчёты тока увлечения в сферическом торе. Розроблено двовимірний код для розрахунку електромагнітного поля швидкої магнітозвукової хвилі в токамаках у діапазоні високих гармонік циклотронної частоти іонів. Використовуючи тороїдальну симетрію плазми токамаків, код знаходить рішення рівнянь Максвела методом скінчених різниць для окремої тороїдальної гармоніки. Граничні умови задаються на реальній стінці камери токамака. ВЧ-антена моделюється введенням «зовнішнього» струму в закон Ампера. Полоїдальне магнітне поле, що утримує, і внесок від «теплової» частини тензора діелектричної проникливості плазми включені в розрахунки за допомогою ітерацій. Код було перевірено шляхом порівняння розрахунків з відомим аналітичним рішенням. Наведено перші розрахунки струму захоплення в сферичному торі.